2019
DOI: 10.1182/bloodadvances.2019031120
|View full text |Cite
|
Sign up to set email alerts
|

Phthalides serve as potent modulators to boost fetal hemoglobin induction therapy for β-hemoglobinopathies

Abstract: Fetal hemoglobin (HbF) induction therapy has become the most promising strategy for treating β-hemoglobinopathies, including sickle-cell diseases and β-thalassemia. However, subtle but critical structural difference exists between HbF and normal adult hemoglobin (HbA), which inevitably leads to reduced binding of the endogenous modulator 2,3-bisphosphoglycerate (2,3-BPG) to HbF and thus increased oxygen affinity and decreased oxygen transport efficiency of HbF. We combined the oxygen equilibrium experiments, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Oxygen (O 2 ) is essential for life [ 1 ] and physiological processes such as cell growth, differentiation, metabolism, and tissue homeostasis [ 2 , 3 ]. Factors such as trauma [ 4 ], blood loss [ 5 ], pernicious anemia [ 6 ] and ischemic cerebrovascular disease [ 7 , 8 ] can decrease tissue oxygen content, lead to hypoxia [ 9 ]. This, in turn, can induce organ dysfunction, particularly in the brain [ 10 ], heart [ 11 ] and kidney [ 12 ] and leading to irreversible damage and/ or death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen (O 2 ) is essential for life [ 1 ] and physiological processes such as cell growth, differentiation, metabolism, and tissue homeostasis [ 2 , 3 ]. Factors such as trauma [ 4 ], blood loss [ 5 ], pernicious anemia [ 6 ] and ischemic cerebrovascular disease [ 7 , 8 ] can decrease tissue oxygen content, lead to hypoxia [ 9 ]. This, in turn, can induce organ dysfunction, particularly in the brain [ 10 ], heart [ 11 ] and kidney [ 12 ] and leading to irreversible damage and/ or death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive ingredients of L. striatum can be divided into four categories: phenols and organic acids (such as ferulic acid), phthalides (such as ligustilide and senkyunolide), alkaloids (such as ligustrazine), and polysaccharides [2] . Recent pharmacological studies have suggested that phthalide molecules are among the most important active substances in L. striatum [3][4][5] . Among these small molecules, senkyunolides may play an essential pharmacodynamic role in vivo because of their high oral bioavailability (BA) and have received extensive attention [6] .…”
Section: Introductionmentioning
confidence: 99%